Popular Constitutionalism and the Rule of Recognition: Whose Practices Ground U.S. Law? - Adler, Matthew D. (2006)
The law within each legal system is a function of the practices of some social group. In short, law is a kind of socially grounded norm. H.L.A Hart famously developed this view in his book, The Concept of Law, by arguing that law derives from a social rule, the so-called “rule of recognition.” But the proposition that social facts play a foundational role in producing law is a point of consensus for all modern jurisprudents in the Anglo-American tradition: not just Hart and his followers in the positivist school, most prominently Joseph Raz and Jules Coleman, but also the anti-positivist Ronald Dworkin, who argues that law necessarily synthesizes moral considerations with social facts. But which group’s practices ground each legal system? In particular, which group’s practices undergird U.S. law? Positivists since Hart have universally pointed to either officials or judges as the “recognitional community” (my term): the group such that its rules, conventions, cooperative activities, or practices in some other sense are the social facts from which the law of a given legal system derives. So Hart and all other positivists would identify either U.S. officials or U.S. judges as the recognitional community for U.S. law. This Article grapples with the tension between the positivist’s official- or judge-centered account of the recognitional community and the “popular constitutionalism” now so widely defended by constitutional scholars such as Larry Kramer, Robert Post, Reva Siegel, Mark Tushnet, Jeremy Waldron, and many others. Surely the popular constitutionalist would want to claim that U.S. citizens, not judges or officials, are the recognitional community for U.S. law. I term this position “deep popular constitutionalism.” Indeed, it turns out that Dworkin’s account of law, in its ambition to generate associative moral obligations for the citizenry as a whole, implies deep popular constitutionalism. Here there is a disagreement, hitherto unnoticed, between Dworkin and the positivists. My solution to this disagreement – to the debate between deep popular constitutionalists and deep official or judicial supremacists -- is to dissolve it by providing a group-relative account of law. Social norms, such as norms of dress or eating, are clearly group-relative. A particular dressing or eating behavior may be socially appropriate relative to one group’s norms, yet socially inappropriate relative to another’s. This Article extends the group-relative view from social norms to law itself, with a particular focus on U.S. law and constitutionalism. Part I surveys the jurisprudential literature. It shows how Hart and successor positivists identify the rule of recognition as a social practice engaged in by officials or some subset of officials (judges), rather than citizens generally, and argues that Dworkin by contrast sees the citizenry as a whole as his recognitional community. Parts II and III defend a group-relative account of law. Part II argues, with reference to the U.S. experience, that multiple groups can simultaneously instantiate the kind of social fact that undergirds law, be it a convention, a social norm, a “shared cooperative activity” (SCA), or something else. At many points in U.S. constitutional history, multiple official or citizen groups, defined along departmental, partisan, regional, state-federal, religious, or other lines, have accepted competing rules of recognition for U.S. law. Part III argues that “law” functions, primarily, as either an explanatory or a normative construct, and that insisting on a single recognitional community for each legal system would be arbitrary, both for explanatory purposes and for normative purposes. Part IV considers the many implications of the group-relative account for U.S. constitutional theory – in particular, for popular constitutionalism